Cutting-Edge Technology for Rapid Bedside Assessment of Capillary Refill Time for Early Diagnosis and Resuscitation of Sepsis - Sheridan, David C.; Cloutier, Robert; Kibler, Andrew; Hansen, Matthew L. (Frontiers in Medicine, 2020)
This manuscript will discuss the broad application of capillary refill to resuscitation care and sepsis in particular for adult patients but much can be applied to pediatrics as well. The authors will then introduce a new technology that has been developed through a problem-based innovation approach to allow clinicians rapid assessment of end-organ perfusion at the bedside or emergency department triage and be incorporated into the electronic medical record. Future applications for identifying patient decompensation in the prehospital and home environment will also be discussed. This new technology has 3 significant advantages: 1) the use of reflected light technology for capillary refill assessment to provide deeper tissue penetration with less signal-to-noise ratio than transmitted infrared light, 2) the ability to significantly improve clinical outcomes without large changes to clinical workflow or provider practice, and 3) it can be used by individuals with minimal training and even in low resource settings to increase the utility of this technology. It should be noted that this perspective focuses on the utility of capillary refill for sepsis care, but it could be considered the next standard of care vital sign for assessment of end-organ perfusion. The ultimate goal for this sensor is to integrate it into existing monitors within the healthcare system.